Safety and efficacy of BAY 94-9027, an extended-half-life factor VIII, during surgery in patients with severe hemophilia A: Results of the PROTECT VIII clinical trial. Issue 183 (November 2019) - Santagostino, Elena; Lalezari, Shadan; Reding, Mark T.; Ducore, Jonathan; Ng, Heng Joo; Poulsen, Lone H.; Michaels, Lisa A.; Linardi, Camila C.G.
Abstract: Introduction: Ensuring hemostasis during invasive procedures is a challenge in patients with severe hemophilia A. This analysis evaluated efficacy and safety of BAY 94-9027, an extended-half-life recombinant factor VIII (FVIII), in the surgical setting. Materials and methods: Patients participating in an open-label BAY 94-9027 clinical trial who underwent major surgery were included in the analysis. Investigator/surgeon assessment of hemostasis during surgery was the primary outcome. In addition, information about FVIII use, FVIII levels during perioperative period, bleeding complications and FVIII inhibitor development were collected. Results: Data were analyzed for 26 major surgeries (orthopedic, n = 21) in 20 patients aged 13–61 years. BAY 94-9027 provided effective hemostasis during all procedures. FVIII levels 6–8 h post preoperative infusion and prior to the first follow-up infusion were in the range expected to maintain protection in the major surgery setting. The median time from preoperative infusion to the first follow-up infusion (the first infusion administered after the preoperative infusion) was 12.33 (3.6–49.9) h. No intraoperative bleeding complications occurred, and no new inhibitors developed following any surgery. Conclusions: The results of the study demonstrate that BAY 94-9027 was efficacious and well tolerated in the treatment of patients undergoing major surgeries. Advantages of BAY 94-9027 include the potential for less frequent infusion and reduced factor consumption, which should simplify the management of patients during major surgery. Highlights: Largest hemophilia A surgery cohort reported receiving extended-half-life treatment. Procedures predominantly orthopedic, typical of those needed by hemophilia patients. Hemostasis with BAY 94-9027 was excellent/good for major surgery bleed prevention. Frequent and/or continuous infusion was not needed during the perioperative period.